In vitro and in vivo evaluation of the biofilm-degrading Pseudomonas phage Motto, as a candidate for phage therapy - Manohar, Prasanth; Loh, Belinda; Turner, Dann; Tamizhselvi, Ramasamy; Mathankumar, Marimuthu; Elangovan, Namasivayam; Nachimuthu, Ramesh; Leptihn, Sebastian (Frontiers in Microbiology, 2024)
Infections caused by Pseudomonas aeruginosa are becoming increasingly difficult to treat due to the emergence of strains that have acquired multidrug resistance. Therefore, phage therapy has gained attention as an alternative to the treatment of pseudomonal infections. Phages are not only bactericidal but occasionally show activity against biofilm as well. In this study, we describe the Pseudomonas phage Motto, a T1-like phage that can clear P. aeruginosa infections in an animal model and also exhibits biofilm-degrading properties. The phage has a substantial anti-biofilm activity against strong biofilm-producing isolates (n = 10), with at least a twofold reduction within 24 h. To demonstrate the safety of using phage Motto, cytotoxicity studies were conducted with human cell lines (HEK 293 and RAW 264.7 macrophages). Using a previously established in vivo model, we demonstrated the efficacy of Motto in Caenorhabditis elegans, with a 90% survival rate when treated with the phage at a multiplicity of infection of 10.